Identification of Novel Microsatellite Markers to Assess the Population Structure and Genetic Differentiation of Ustilago hordei Causing Covered Smut of Barley - Kashyap, Prem Lal; Kumar, Sudheer; Kumar, Ravi Shekhar; Tripathi, Rahul; Sharma, Palika; Sharma, Anju; Jasrotia, Poonam; Singh, Gyanendra Pratap (Frontiers in Microbiology, 2020)
Barley covered smut (CS) pathogen Ustilago hordei genome was mined for microsatellite distribution and their application in defining population structure and genetic variation. To dissect the molecular variation and genetic structure of U. hordei, 59 fungal isolates representing two distinct agro-ecological zones of India were analyzed by employing simple sequence repeats (SSRs). Using bioinformatic approaches, a total of 100239 and 137442 microsatellites were identified from 20.13 and 26.94 Mb of assembled genomic sequences of Uh364 and Uh4857-4 isolates of U. hordei, respectively. Penta-nucleotides (31.29 and 29.75%) followed by tri-nucleotide (28.27 and 29.88%) were most prevalent in both the genomes. Out of them, fifteen polymorphic microsatellites showing conservancies in both the genomes were selected for exploring population genetic structure of U. hordei. An average of two alleles per microsatellite marker was generated with band size ranged from 180-850 bp. Polymorphic information content (PIC) varied between 0.095-0.37. Fifty-nine isolates were distributed in two distinct groups with about 65% genetic similarity according to UPGMA clustering and population structure analysis (K = 2). Gene flow analysis (Nm = 1.009) reflected restricted gene flow among the analyzed population. An AMOVA analysis displayed high level of genetic variation within population (87%) and low variation among populations (13%). Linkage disequilibrium (LD) analysis indicated positively significant but relatively low SIA value in both the population sets [standardized index of association (SIA) = 0.181], advocating a state of LD with epidemic population structure. In conclusion, the newly developed neutral SSR markers are highly polymorphic within U. hordei and will be useful for revealing evolutionary history and providing deep insight into the population dynamics of U. hordei in India and also facilitate in developing management strategies for CS of barley.